Regeneration of pancreatic insulin-producing cells by in situ adaptive cell conversion. (October 2016) - Chera, Simona; Herrera, Pedro L
Abstract : The impaired ability to produce or respond to insulin, a hormone synthetized by the pancreatic β-cells, leads to diabetes. There is an excruciating need of finding new approaches to protect or restore these cells once they are lost. Replacement and ex vivo directed reprogramming methods have an undeniable therapeutic potential, yet they exhibit crucial flaws. The in vivo conversion of adult cells to functional insulin-producing cells is a promising alternative for regenerative treatments in diabetes. The stunning natural transdifferentiation potential of the adult endocrine pancreas was recently uncovered. Modulating molecular targets involved in β-cell fate maintenance or in general differentiation mechanisms can further potentiate this intrinsic cell plasticity, which leads to insulin production reconstitution.